EFEKTIVITAS MODEL FLIPPED CLASSROOM DALAM PROSES PEMBELAJARAN KONSEP DASAR MATEMATIKA DI SEKOLAH DASAR - Suliyasti, Desi; Umalihayati, Umalihayati; Rachman, Aditya; Maidila, Nia; Hidayah, Nova Nurul (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This article discusses the effectiveness of the Flipped Classroom model in the learning process in elementary schools, especially in understanding mathematical concepts.  This model has been proven to be able to increase students' learning independence and their learning outcomes.  Previous research also shows that this model is effective in improving students' abilities significantly.  The research method used is a literature review from various relevant sources.  The research results show that the Flipped Classroom model can increase students' interest in learning and their ability to understand mathematical concepts.  Several components that influence the success of this model include good interaction between educators and students, the use of technology that supports learning, students' ability to interact and interact, and easy access to online teaching materials.  The Flipped Classroom model allows students to study learning material at home before class meetings, so that class time can be used for more in-depth discussion and application of the material.  The teacher's role in this model is as a facilitator who guides students in the learning process.  Thus, the Flipped Classroom model can be used as an effective alternative in improving student learning outcomes in elementary schools, especially in understanding mathematical concepts